Enhancing sport performance: Merging sports science with coaching - Meyers, M. C. (International Journal of Sports Science and Coaching, 2006)
Over the years, sport science has mainly been viewed by coaches as inaccessible, too technical, or in many cases, non-applicable to the actual sport setting. With the renewed focus on prevention of injuries, on enhancing performance at the younger levels of competition, and on the extensive amount of time and financial commitment toward training and conditioning, taking a more comprehensive approach through science provides the coach, as well as the athlete, greater control, preparation, accountability and, most importantly, measurable progress. It is the merging of 'science and sweat' that will allow today's athletes to not only excel and compete at much higher levels, but minimize predisposition to injury and enhance career longevity. This article describes and revisits some scientific areas and tools to add to a coach's present arsenal of assessments, and discusses the advantages, complexities, and concerns in the continually evolving area of sport science.